PELANGGARAN JANJI KAWIN BERDASARKAN PASAL 29 UNDANG-UNDANG NOMOR 1 TAHUN 1974 DITINJAU MENURUT PASAL 1365 KITAB UNDANG-UNDANG HUKUM PERDATA - Pangaribuan, Maruli Oscar (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT            Marriage is a bond between the inner and outer man with one woman as husband and wife with the intention of forming a family (household) a happy eternal based on God. Married according to its original meaning is sexual intercourse but by the meaning mazasi (mathaporic) or legal sense is contract (agreement) which justify the marital sexual relationship as between a man and a woman.            Of the many benefits of marriage contained therein, it is encouraging more people to carry out the marriage which is also called as worship, but before implementing it 's own marriage in the society of the young couple usually establish love in a relationship of lovers, they mutually bind themselves by promises appointments, including to build a household. Promise of marriage were spoken of couples who are dating is usually only orally and in the absence of written evidence, if one of the parties deny it, it will be difficult to hold him accountable. Broken promise spoken by the male to the female, it is certainly very harmful for women.            In Article 29 of Law No. 1 of 1974 regulates mating promise or promises made between the bride and groom prior to or at the time the marriage took place. One party reneges on the promise of marriage that has been made will harm other parties who have committed themselves to the marriage promise broken by works done by one of the parties is an unlawful act that causes harm to the other party, as provided in Article 1365 of the Civil Code.            Mating the broken promise made is a tort, but when the promise was denied prior to the announcement of the marriage, according to Article 58 of the Civil Code, the promise of marriage does not have any legal effect. However, if the promise of marriage was followed by the announcement of the implementation of the marriage, then the marriage can be prosecuted broken promises upfront judge, for not fulfilling the promise of marriage as a violation of religious norms and morality in society. The need for regulation of broken promises mating in the Act No. 1 of 1974 on Marriage as laws governing marriage nationally and be a reference for the various groups in society because of broken promises mating arrangements in Article 58 of the Civil Code does not provide legal protection for women, thus providing an opportunity for men who do not abuse it for good purposes.